Influence of Sample Size in Land Cover Classification Accuracy Using Random Forest and Sentinel-2 Data in Portugal - Moraes, Daniel (2021)
Moraes, D., Benevides, P., Costa, H., Moreira, F. D., & Caetano, M. (2021). Influence of Sample Size in Land Cover Classification Accuracy Using Random Forest and Sentinel-2 Data in Portugal. In IGARSS 2021 - 2021 IEEE International Geoscience and Remote Sensing Symposium: Proceedings (pp. 4232-4235). IEEE. https://doi.org/10.1109/IGARSS47720.2021.9553924